A Rare Case of Bacterial Meningitis Caused by Hematogenous Spread of Vancomycin-Resistant Enterococcus faecium in an Immunocompromised Patient - Myeongji Kim; Christopher Graham; Ryan W. Stevens; Aditya Shah (Case Reports in Infectious Diseases)
Vancomycin-resistant Enterococcus faecium (VRE) meningitis is rare. It is usually associated with neurosurgical procedures or devices. We describe a case of VRE meningitis from hematogenous spread during persistent bacteremia in an immunocompromised patient who received haploidentical bone marrow transplant for VEXAS syndrome. The bacteremia and meningitis were successfully treated with combination of intravenous (IV) daptomycin, ceftaroline, and linezolid.